Domestic legislatures and international human rights law: Legislating on religious symbols in Europe. Issue 4 (1st October 2016) - Squatrito, Theresa
ABSTRACT: This article examines the dynamics of domestic legislatures' application of international human rights law. Specifically, this article asks the following: What factors shape how domestic legislatures apply international human rights law while they enact national law and policy? Lawmakers have a variety of motives for invoking and deliberating international law. Given these motives, the article identifies two factors — civil society actors and legal experts and the flexibility of international law — that are likely to contribute to if and how national legislatures interpret and apply international human rights law while legislating. These factors are examined through case studies on religion in schools in the United Kingdom, Germany, and France. This article argues civil society actors and legal experts and the flexibility of international law inform lawmakers' estimation of political costs related to compliance and thus how they apply international human rights law to domestic legislation.